Internal quality assurance system (IQAS) as an effort to create a superior Islamic boarding school - Istikomah Istikomah; Taufik Churrahman; Budi Haryanto; Nurul Hadi (Community Empowerment, 2021)
The success of Islamic boarding schools in producing quality graduates, one of which is related to the quality standards set. One of the quality indicators is the ownership of the Islamic Boarding School's Internal Quality Assurance System (SPMI) document. The purpose of this community service is to socialize the importance of SPMI for the An-nur Muhammadiyah Islamic boarding school, Sidoarjo. This school is relatively new, but has a vision of becoming a quality Islamic boarding school. Meanwhile, the stakeholders, both mudir, asatidz-asatidzah council, and their education staff do not yet have an understanding of the importance of SPMI for institutions, and do not yet have an SPMI. The service method used is to provide assistance and training in the preparation of the SPMI instrument which consists of 8 criteria. As a result, all stakeholders of An-Nur Islamic boarding school understand the importance of SPMI and the formation of the SPMI organization. In addition, partners are able to develop SPMI instruments independently and can implement them in order to achieve the expected quality of Islamic boarding schools